Graft endoclamping with brachio-femoral wire conduit for elephant trunk retrieval in open thoraco-abdominal aortic repair. (16th November 2020) - Gatta, Emanuele; Berretta, Paolo; Carbonari, Luciano; Di Eusanio, Marco
Abstract: Staged repair involving aortic arch replacement with elephant trunk (ET) technique and thoraco-abdominal aorta (TAA) replacement is the treatment of choice for patients with extensive aortic disease. The ET graft serves as a proximal platform for subsequent distal aortic repair as it allows one to avoid hazardous dissection of the distal arch and facilitate proximal anastomosis. However, in patients with large proximal descending aorta aneurysm, identifying and retrieving the ET during the second-stage TAA intervention can be challenging because of an unclampable aorta. Here, we present our brachio-femoral wire conduit technique for a safe ET clamping and retrieval during second-stage TAA procedures.